Social Construction of Disability - Putri, Rizka Julia; Marsa, Yummy Jumiati (Papanda Publisher, 2025)
This study examines the social reality of people with disabilities in Batang Kuis using Berger and Luckmann's social construction theory, which includes the processes of externalization, objectification, and internalization. The method used is qualitative with a descriptive approach, which is to describe and understand social phenomena, behavior, or certain conditions in the research problem formulation. Data was obtained through observation, semi-structured interviews with people with disabilities, as well as relevant literature and documentation studies. The purpose of this research is to gain a deep understanding of how people with disabilities live their lives and how social structures shape their experiences and realities. This research was conducted between April and May 2025. People with disabilities in Batang Kuis Subdistrict are beginning to be socially accepted through empathetic interactions, reflecting a process of internalization in social construction. However, this acceptance has not been followed by objectification in the form of adequate policies, facilities, and public services. The lack of access to inclusive education, therapy, and vocational training highlights the weakness of structural support. Therefore, strengthening policies and community education is necessary to ensure that acceptance does not remain at a symbolic level but transforms into real and sustainable inclusion.